The Poetry and Prose of Wang Wie. Volume 1 (Library of Chinese Humanities, 2020)
Wang Wei has traditionally been considered one of the greatest of Tang dynasty poets, together with Li Bo and Du Fu. This is the first complete translation into English of all of his poems, and also the first substantial translation of a selection of his prose writings. For the first time, readers encountering his work in English translation will get a comprehensive understanding of Wang Wei's range as a poet and prose writer. In spite of the importance of Wang Wei's poetry in the history of Chinese literature, no one has attempted a complete translation of all of his surviving poems moreover, even though he was known for his skill in composing prose pieces in the recognized genres of his day (especially as a writer of commissioned compositions), very little of his prose has been translated. This translation will enable students with limited or no knowledge of Chinese to get a full sense of Wang Wei's compositional range. Moreover, since Wang Wei was known for being a devout Buddhist, having the complete poetry available in reliable translation as well as all of the prose that is connected to the Buddhist faith will be useful to students of Chinese religion.